The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4161/isl.25459
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the involvement of GPR40 and NADPH oxidase in palmitic acid-induced superoxide production and insulin secretion

Abstract: G protein coupled receptor 40 (GPR40) and nicotinamide adenine dinucleotide phosphate (NADPH) oxidase complex have been shown to be involved in the fatty acid amplification of glucose-stimulated insulin secretion (GSIS). The effect of palmitic acid on superoxide production and insulin secretion by INS-1E cells and the possible involvement of GPR40 and NADPH oxidase in these processes were examined in this study. Cells were incubated during 1 h with palmitic acid in low and high glucose concentrations, a GPR40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 56 publications
(78 reference statements)
1
26
0
Order By: Relevance
“…7B). Sodium palmitate is thought to stimulate insulin release by interaction with the FFA receptor FFAR1/GPR40 and via increased long-chain Acyl-CoA esters, and longterm palmitate effects are known to be deleterious for beta-cells [22,32,33]. We observed that palmitate-stimulated insulin release was decreased by GLX351322 at a concentration of 2 µM (Fig.…”
Section: Acute Effects Of the Nox Inhibitors Gkt-136901 And Glx351322mentioning
confidence: 48%
See 1 more Smart Citation
“…7B). Sodium palmitate is thought to stimulate insulin release by interaction with the FFA receptor FFAR1/GPR40 and via increased long-chain Acyl-CoA esters, and longterm palmitate effects are known to be deleterious for beta-cells [22,32,33]. We observed that palmitate-stimulated insulin release was decreased by GLX351322 at a concentration of 2 µM (Fig.…”
Section: Acute Effects Of the Nox Inhibitors Gkt-136901 And Glx351322mentioning
confidence: 48%
“…Thus, it may be that insulin release is stimulated in the 4 short term by increased ROS production, whereas a long-term NOX-activation leads to loss of beta-cell function. Not only glucose in vitro or hyperglycemia in vivo promotes beta-cell activation of NOX, but also sodium palmitate, a free fatty acid which is increased in Type 2 diabetes, and which stimulates the release of insulin in short-term experiments, but inhibits beta-cell function after a prolonged exposure period [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin can affect many systems in the cell, such as the mitochondrial metabolism (Ramis et al 2015); hence, it is plausible that the absence of melatonin may induce ROS production not only through NOX but also through other oxidant sources, such as the mitochondria. However, it is important to consider that DHE is a specific probe for the detection of cytosolic ROS content (Zhao et al 2003, Dikalov 2011, and previous publications have already shown that most of the ROS products generated after glucose stimulation are superoxide, which was confirmed using SOD linked to polyethylene glycol (PEG-SOD) (Graciano et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Recent evidence shows that insulin secretion is inversely related to ROS concentration (Rebelato et al 2011, Graciano et al 2013. Under low glucose, high ROS content limits insulin secretion to basal levels (Munhoz et al 2016).…”
Section: :3mentioning
confidence: 99%
See 1 more Smart Citation